2023
DOI: 10.5455/javar.2023.j657
|View full text |Cite
|
Sign up to set email alerts
|

New probiotics (Lactobacillus plantarum and Saccharomyces cerevisiae) supplemented to fermented rice straw-based rations on digestibility and rumen characteristics in vitro

Abstract: Objective: This research was arranged to explore the effect of supplementation of a combination of Lactobacillus plantarum and Saccharomyces cerevisiae as a new probiotic in fermented rice straw-based rations on in vitro digestibility and ruminal characteristics. Materials and Methods: A randomized group design with 3 types of treatment and 4 replications as a group was used in this study. A probiotic inoculum containing L. plantarum and S. cerevisiae with 1 × 1010 colony-forming unit (CFU)/ml. Treatments wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…Increased digestibility in ruminant livestock shows that nutrients that can be broken down by microbes in the rumen are also increasing [ 19 ]. The increase in OM followed the increase in DM [ 19 , 20 ]. The findings of this study align with Phesatcha et al research [ 21 ], which suggested that feed ingredients with lower fiber content are more easily digestible due to their thin cell walls, making them more susceptible to breakdown by active microorganisms in the rumen.…”
Section: Resultsmentioning
confidence: 99%
“…Increased digestibility in ruminant livestock shows that nutrients that can be broken down by microbes in the rumen are also increasing [ 19 ]. The increase in OM followed the increase in DM [ 19 , 20 ]. The findings of this study align with Phesatcha et al research [ 21 ], which suggested that feed ingredients with lower fiber content are more easily digestible due to their thin cell walls, making them more susceptible to breakdown by active microorganisms in the rumen.…”
Section: Resultsmentioning
confidence: 99%
“…Measuring total gas in vitro can be used to detect the decomposition of organic matter, particularly nitrogen and carbon [ 20 , 25 ]. The increase in total gas produced when herbal plants are combined shows that it does not affect microbial activity in gas production.…”
Section: Resultsmentioning
confidence: 99%